Etnografías de las cárceles bonaerenses - Galvani, Iván (Coord.) (Conflicto, violencia y política, 2022)
As the second volume of the collection Violence, security and social issues, this book presents a series of recent ethnographic studies on the prison establishments of the Prison Service of the Province of Buenos Aires (Servicio Penitenciario Bonaerense, SPB). In line with the initial proposal of this first series of the collection, this set of articles have their origin in the most prominent final papers for the Bachelor's degree in Sociology from the National University of La Plata (Universidad Nacional de La Plata, UNLP), which have been discussed within the framework of the Center for Security Studies in the Province of Buenos Aires (Núcleo de Estudios sobre Seguridad en la provincia de Buenos Aires, NESBA), a group formed around the sustained participation in various research projects at the School of Humanities and Education Sciences in UNLP. These studies share an interest in analyzing the social relations developed inside prison establishments, as well as those that connect the inhabitants of these institutions with other actors and spaces of the rest of society.